The Prognostic Value of ctDNA and bTMB on Immune Checkpoint Inhibitors in Human Cancer - Wei, Jiayan; Feng, Jia; Weng, Yiming; Xu, Zexi; Jin, Yao; Wang, Peiwei; Cui, Xue; Ruan, Peng; Luo, Ruijun; Li, Na; Peng, Min (Frontiers in Oncology, 2021)
Background: Circulating tumor DNA (ctDNA) levels and blood tumor mutation burden (bTMB) have a significant impact on the prognosis of tumor patients. However, their prognostic role in immune checkpoint inhibitors (ICIs) in cancer patients is still unclear. Methods: We used Review Manager software (version 5.3) to perform a meta-analysis based on the published literature to explore the prognostic value of ctDNA and bTMB on patients receiving immunotherapy. We extracted the hazard ratios (HRs) of progression-free survival (PFS) and overall survival (OS) for each included study and their respective 95% confidence intervals (CIs) and P values for analysis. Results: 13 studies were included in the meta-analysis. Higher ctDNA levels were significantly associated with shorter OS (HR, 3.35; 95%CI, 2.49-4.51; P <0.00001) and PFS (HR, 3.28; 95%CI, 2.47-4.35; P <0.00001). The results of ctDNA subgroup analysis showed that post-treatment high-level ctDNA significantly correlated with shorter OS in cancer patients receiving ICIs (HR, 5.09; 95%CI, 1.43-18.07; P = 0.01). Moreover, patients with ctDNA clearance had better OS (HR, 4.94; 95%CI, 2.96-8.26; P <0.00001). Patients with high post-treatment ctDNA levels had shorter PFS (HR, 3.00; 95%CI, 2.02-4.46; P <0.00001), and patients with ctDNA clearance had longer PFS (HR, 4.61; 95%CI, 2.78-7.65; P <0.00001). However, there was no statistically significant difference in OS benefits between high and low bTMB after ICI therapy (HR, 0.68; 95%CI, 0.33-1.37; P = 0.28). Conclusions: The host immune system and tumor burden together determine whether cancer patients can benefit from ICI therapy. Our systematic review and meta-analysis revealed for the first time that pretreatment ctDNA levels, post-treatment ctDNA levels and clearance of ctDNA can independently be used as prognostic factors for anti-tumor immunotherapy, while bTMB cannot. In conclusion, ctDNA levels have great potential as an assistant tool for radiologic assessments to make clinical therapeutic decisions. The prognostic utility of bTMB still requires further exploration.